CORRELATION BETWEEN DIET QUALITY AND BODY COMPOSITION WITH WORK FATIGUE IN FEMALE WORKERS - Atmaka, S.Gz, MPH, Dominikus Raditya; Arini, Shintia Yunita; Khoiroh, Mawadatul (Media Gizi Indonesia, 2025)
Introduction: In 2020, labor force participation rate for women in East Java province was 70,0%, and in Lumajang district reached 66,19%. Women usually have a higher fat mass compared to men. Body composition dominated by fat mass can reduce oxygen distribution process, can cause anaerobic energy metabolism which produce lactic acid as ﬁnal product and causes fatigue. Low diet quality is related with high energy and fat intake which will result in body fat mass elevation and work fatigue. This study aimed to determine the correlation between diet quality and body composition with work fatigue. Method: This study used cross sectional design with total respondents of 120 female workers in production division of wood factory. Collected data were means of anthropometric measurements (weight, height, upper arm circumference, and abdominal circumference), Semi Quantitative Food Frequency Questionnaire, and Subjective Self Rating Test. Correlation test used were Chi square test continued with Pearson correlation test. Result: Result showed a significant correlation between work fatigue and total sodium intake per day (p=0.040), total saturated fat intake (p=0.037), Body Mass Index (p<0.001), abdominal circumference (p<0.001), and upper arm circumference (p=0.002). Conclusion: Improving diet quality and decreasing body fat mass can reduce work fatigue.